Dome reconstruction in a rare case of alar cartilage agenesis of the middle and lateral crura - Bran, Gregor M.; Riedel, Frank (Aesthetic plastic surgery, 2016)
Congenital deformities of the nasal cartilage are extremely rare. Often, they remain undiscovered until an open approach is completed during rhinoplasty. We present a case of unilateral congenital agenesis of the middle and lateral crura of the alar cartilage. A new concept for dome reconstruction using conchal cartilage is introduced. Additionally, current concepts of embryology are summarized, which will help understanding the pathophysiology of such rare deformities.Level of Evidence VThis journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266.